An [FeIII8] molecular oxyhydroxide. Issue 23 (25th May 2022) - Cutler, Daniel J.; Coletta, Marco; Singh, Mukesh K.; Canaj, Angelos B.; McCormick, Laura J.; Coles, Simon J.; Schnack, Jürgen; Brechin, Euan K.
Abstract : An [Fe III 8 ] hexagonal bipyramid displays antiferromagnetic exchange between the two capping tetrahedral ions and the six ring octahedral ions resulting in a spin ground state, S = 10. Abstract : An [Fe III 8 ] hexagonal bipyramid displays antiferromagnetic exchange between the two capping tetrahedral ions and the six ring octahedral ions resulting in a spin ground state of S = 10.